Hubungan Perilaku Pemeliharaan Kebersihan Gigi Dan Mulut Dengan Gingivitis Pada Pasien Di Puskesmas Julok - Zuratu Ramadhani; Nasri Nasri (Journal of Innovative and Creativity (Joecy), 2026)
Based on patient visit data at the Julok Community Health Center (Puskesmas), cases of gingivitis have shown an upward trend over the past two years. In 2024, 327 cases of gingivitis were recorded, representing approximately 27.4% of total dental service visits. Meanwhile, in 2025, the number of cases rose to 356, or about 29.1% of total visits. Therefore, this study aimed to determine the relationship between oral and dental hygiene maintenance behavior and gingivitis among patients at Julok Public Health Center, East Aceh Regency. This study employed a quantitative research method with a cross-sectional design. The study population consisted of all patients visiting the Dental Clinic of Julok Public Health Center, with an average monthly attendance of 120 patients. The sample consisted of 55 respondents, determined using the Slovin formula and selected through purposive sampling. Data were analyzed using univariate and bivariate analyses with the Chi-Square test at a significance level of α = 0.05. The results showed that most respondents had a moderate level of oral and dental hygiene maintenance behavior, accounting for 21 respondents (38.2%). Meanwhile, the highest proportion of respondents experienced mild gingivitis, with 20 respondents (36.4%). The Chi-Square analysis produced a χ² value of 16.27 with a p-value of 0.003 (p < 0.05), indicating a statistically significant relationship between oral and dental hygiene maintenance behavior and gingivitis among patients at Julok Public Health Center, East Aceh Regency. Conclusion: There is a significant relationship between oral and dental hygiene maintenance behavior and gingivitis among patients at Julok Public Health Center, East Aceh Regency.